Effect of Purple Variety Sweet Potato (Ipomoea batatas L.) Anthocyanin on Expression of Estrogen Receptor-Α and Endometrium Thickness on Uterus of Female White Rats (Rattus norvegicus) Exposed to Cigarette Smoke: Effect of Purple Variety Sweet Potato - Wahyu Utami, Syahrida; Ratnawati, Retty; Arsana Wiyasa, I Wayan (Iranian Journal of Pharmaceutical Sciences, 2018)
Cigarette smoke contains around 4000 chemical substances including free radicals and carcinogens, which are xenobiotic agents in the body, affecting the reproductive system. Purple sweet potatoes contain the color pigment anthocyanin. The purple color pigment (anthocyanin) in purple sweet potatoes is a beneficial antioxidant because it can react with free radicals that can cause damage in the body. The goal of the research was to understand the effects of purple variety sweet potato (Ipomoea Batatas L) anthocyanin on the expression of estrogen receptor-α in the endometrium and endometrium thickness on white rats (Rattus norvegicus) exposed to cigarette smoke. The White rats used for the 5 groups were 30 white rats. Exposure to cigarette smoke was given at a rate of 2 sticks/day (each cigarette ± 4 minutes), for 8 weeks after the rats were found to be in the proestrus phase. Endometrium thickness was examined and measured using a Dot slide Olympus XC 10 light microscope and the Olyvia software. Expression of ER-α in the endometrium was measured by using the antibody ER-α (C-311) SC-787 and the immunohistochemistry and calculated by the Immunoratio software. Data were analyzed with the Shapiro-Wilk’s test, t-test and one-way ANOVA (F test). It was found that the average value of ER-α expression in the endometrium for the treatment group given purple variety sweet potato anthocyanin of a dose of 40 mg/Kg BW (15.51 ± 2.65) could increase ER-α expression in the endometrium of female white the rats exposed to cigarette smoke. The average value of endometrium thickness for the treatment group given purple variety sweet potato anthocyanin at a dose of 40 mg/Kg BW (152.51±9.59 μm) showed an increase in the endometrium thickness of female white rats exposed to cigarette smoke. The dose of purple variety sweet potato anthocyanin that could increase ER-α expression in the endometrium and endometrium thickness of rats exposed to cigarette smoke was a dose of 40 mg/Kg BW. The higher the dose of purple variety sweet potato anthocyanin, the greater the effect on the prevention of the reduction of estrogen receptor-α expression and the prevention of the reduction of endometrium thickness on female white rats exposed to cigarette smoke.